2022
DOI: 10.1155/2022/9102145
|View full text |Cite
|
Sign up to set email alerts
|

The Characteristics of Thunderstorms and Their Lightning Activity on the Qinghai-Tibetan Plateau

Abstract: This paper discusses the temporal and spatial distribution characteristics of cloud-to-ground (CG) lightning activity over the Qinghai-Tibetan Plateau (QTP) from 2009 to 2018 and their dependence on meteorological factors. It is found that (1) the number of CG flashes fluctuates, reaches a maximum in 2014, and then gradually decreases. The main active period of CG lightning is from June to September each year, after which it decreases rapidly. CG lightning is mainly distributed in the valley areas at around 48… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Deep convective systems (DCSs with 20 dBZ radar echo tops exceeding 14 km) [25] often cause extreme weather processes such as winds, heavy precipitation, hail, and so on, accompanied by thunderstorms and lightning. In particular, the Tibetan Plateau has unique characteristics of lightning and DCSs [26], and it is very different from the CELR of China at the same latitude [9]. So, studying the relationship between lightning and the DCSs' background over the Tibetan Plateau is of great significance.…”
Section: Convection Background and Comparative Analysismentioning
confidence: 99%
“…Deep convective systems (DCSs with 20 dBZ radar echo tops exceeding 14 km) [25] often cause extreme weather processes such as winds, heavy precipitation, hail, and so on, accompanied by thunderstorms and lightning. In particular, the Tibetan Plateau has unique characteristics of lightning and DCSs [26], and it is very different from the CELR of China at the same latitude [9]. So, studying the relationship between lightning and the DCSs' background over the Tibetan Plateau is of great significance.…”
Section: Convection Background and Comparative Analysismentioning
confidence: 99%
“…Research has demonstrated the apparent dependence of lightning activity on climatic and geographic conditions in diferent regions [18,19,26,27]. Terefore, we selected four typical thermodynamic and moisture factors which are closely related to lightning formation, namely, 2 m temperature, average relative humidity between 3 km and 5 km (3-5 km RH), convective available potential energy (CAPE), and convective inhibition (CIN).…”
Section: Meteorological Datamentioning
confidence: 99%
“…Zhao et al [18] investigated the impact of environmental conditions on positive CG distribution of the warm season in Sichuan Province. Hui et al [19] analyzed the spatiotemporal distribution of CG lightning over the Qinghai-Tibetan Plateau and further discussed their dependence on meteorological factors.…”
Section: Introductionmentioning
confidence: 99%